A Study on Chemical Characterization and Biological Abilities of Alstonia boonei Extracts Obtained by Different Techniques - Adriano Mollica; Gokhan Zengin; Kouadio Ibrahime Sinan; Marcella Marletta; Stefano Pieretti; Azzurra Stefanucci; Ouattara Katinan Etienne; József Jekő; Zoltán Cziáky; Mir Babak Bahadori; Carene Picot-Allain; Mohamad Fawzi Mahomoodally (MDPI AG, 2022)
In the quest for novel therapeutic agents from plants, the choice of extraction solvent and technique plays a key role. In this study, the possible differences in the phytochemical profile and bioactivity (antioxidant and enzyme inhibitory activity) of the Alstonia boonei leaves and stem bark extracted using water, ethyl acetate and methanol, and different techniques, namely infusion, maceration and Soxhlet extraction, were investigated. Data collected showed that methanol extracts of both A. boonei leaves (48.34-53.08 mg gallic acid equivalent [GAE]/g dry extract) and stem bark (37.08-45.72 mg GAE/g dry extract) possessed higher phenolic content compared to the ethyl acetate extracts (leaves: 30.64-40.19 mg GAE/g; stem bark: 34.25-35.64 mg GAE/g). The methanol extracts of A. boonei leaves showed higher radical scavenging and reducing capacity, and these findings were in accordance with phenolic content results. In general, water extracts of A. boonei leaves and stem bark obtained by infusion were poor inhibitors of acetylcholinesterase, α-amylase, α-glucosidase, and tyrosinase, except for butyrylcholinesterase. The chemical profiles of the extracts were determined by UHPLC-MS and the presence of several compounds, such as phenolic acids (caffeic, chlorogenic and ferulic acids, etc.), flavonoids (rutin and isoquercetin) and flavonolignans (Cinchonain isomers). Cell viability was tested using the human peripheral blood monocytic cell line (THP-1), and the extracts were safe up to 25 μg/mL. In addition, anti-inflammatory effects were investigated with the releasing of IL-6 TNF-α and IL-1β. In particular, stem bark extracts exhibited significant anti-inflammatory effects. Data presented in this study highlight the key role of solvent choice in the extraction of bioactive secondary metabolites from plants. In addition, this study appraises the antioxidant and enzyme inhibitory action of A. boonei leaves and stem bark, which are extensively used in traditional medicine.